Pemanfaatan Bioelectrical Impedance Analysis (BIA) untuk Pengukuran Body Fat dan Visceral Fat yang Terasosiasi pada Resiko Penyakit Jantung - Agustiyawan Agustiyawan; Heri Wibisono; Raisha Muthia Azahra; Hana Julian Siregar; Gibran Ghani; Ananda Putri Rifanty (Malahayati Nursing Journal, 2025)
ABSTRACT The prevalence of obesity and the increase in visceral fat in the last decade has become a global health concern, especially in relation to cardiovascular disease risk. Visceral fat, which is stored around vital organs in the abdominal cavity, is more harmful than subcutaneous fat due to its association with insulin resistance, chronic inflammation, and increased risk of cardiovascular disease. Although many studies have addressed obesity, there is a gap in understanding the distribution of body fat, particularly visceral fat, in urban populations undergoing dietary changes. This study aims to explore the distribution of body fat and visceral fat levels and their association with heart disease risk in Saga Village, Balaraja Subdistrict, Tangerang Regency. The study used a cross-sectional design with 433 respondents taken from the population using the Slovin sampling technique. Data were collected through surveys and observations using Bioelectrical Impedance Analysis (BIA) to measure body fat and visceral fat, as well as measurements of blood pressure, cholesterol levels, and blood sugar. The results showed a mean body fat of 13.45 ± 3.42 and visceral fat of 9.24 ± 7.76, indicating a significant proportion of individuals with body and visceral fat accumulation. The prevalence of hypertension at 72% and heart disease at 83% reflects the high health risks in this population. Correlation analysis showed a significant positive association between body fat, visceral fat, and heart disease risk (p 0.05). There was a significant association between body fat and visceral fat with heart disease risk, suggesting the importance of understanding body fat distribution in cardiovascular risk assessment. Further research is recommended to focus on the prospective relationship between body fat, visceral fat, and cardiovascular disease risk. Keywords: Bioelectrical Impedance Analysis, Body Fat, Cardiovascular, Visceral Fat  ABSTRAK Prevalensi obesitas dan peningkatan lemak viseral dalam dekade terakhir telah menjadi perhatian kesehatan global, terutama terkait risiko penyakit kardiovaskular. Lemak viseral, yang tersimpan di sekitar organ vital dalam rongga perut, lebih berbahaya dibandingkan lemak subkutan karena kaitannya dengan resistensi insulin, inflamasi kronis, dan peningkatan risiko penyakit kardiovaskular. Meskipun banyak penelitian telah membahas obesitas, terdapat kesenjangan pemahaman tentang distribusi lemak tubuh, khususnya lemak viseral, pada populasi urban yang mengalami perubahan pola diet. Penelitian ini bertujuan untuk mengeksplorasi distribusi tingkat body fat dan visceral fat serta hubungannya dengan risiko penyakit jantung di Desa Saga, Kecamatan Balaraja, Kabupaten Tangerang. Penelitian menggunakan rancangan cross-sectional dengan 433 responden yang diambil dari populasi menggunakan teknik sampling Slovin. Data dikumpulkan melalui survei dan observasi menggunakan Bioelectrical Impedance Analysis (BIA) untuk mengukur body fat dan visceral fat, serta pengukuran tekanan darah, kadar kolesterol, dan gula darah. Hasil penelitian menunjukkan rerata body fat sebesar 13,45 ± 3,42 dan visceral fat 9,24 ± 7,76, yang menunjukkan proporsi signifikan individu dengan akumulasi lemak tubuh dan viseral. Prevalensi hipertensi sebesar 72% dan penyakit jantung sebesar 83% mencerminkan tingginya risiko kesehatan pada populasi ini. Analisis korelasi menunjukkan adanya hubungan positif yang signifikan antara body fat, visceral fat, dan risiko penyakit jantung (p 0,05). Terdapat hubungan signifikan antara body fat dan visceral fat dengan risiko penyakit jantung, menunjukkan pentingnya pemahaman distribusi lemak tubuh dalam penilaian risiko kardiovaskular. Penelitian lanjut disarankan untuk fokus pada hubungan prospektif antara body fat, visceral fat, dan risiko penyakit kardiovaskular. Kata Kunci: Bioelectrical Impedance Analysis, Body Fat, Kardiovaskular, Visceral Fat